UTILIZING FOREIGN EXPERIENCE IN HIGHER EDUCATION INSTITUTIONS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
This article discusses the issue and solution of ensuring the quality of training in higher education institutions and improving the quality of education and monitoring in current higher education institutions based on foreign experiences. It suggests the importance of incorporating international expertise and practices into educational institutions at the higher education level. This can be achieved by adopting and adapting foreign experiences, methods, and approaches to enhance the quality of education and provide students with a global perspective.